Assessment of Level of Depression, Anxiety and Stress among Hypertensive Patients (Medico Legal Update, 2020)
Assessment of the level of depression, anxiety and stress among hypertensive patients attending MedicineOPD, in selected Tertiary Care Hospital, Kanchipuram District, Tamil Nadu, India. The objectives were toassess the level of depression, anxiety and stress among hypertension patients and to associate the selecteddemographic variables with the level of depression, anxiety and stress of hypertension patients. 80 patientswere selected using by purposive sampling technique. We have used DASS-21 standardized tool for ourresearch study. The study findings showed that majority of the patients 64(80%) were normal, 13(16%) weremildly depressed and only 3(4%) were moderately depressed, On the aspects of anxiety majority 58(73%)were normal, 13(16%) were having mild anxiety and only 9(11%) were having moderate anxiety and onthe level of stress majority 75(94%) were normal and 5(6%) were mildly stressed. Over all mean of levelof depression of hypertensive patients were found to be (6.67), for the level of anxiety the mean was foundto be (5.7) and (8.9) for the level of stress aspects of the of the hypertensive patients. Standard deviationaspects of the hypertensive patients for the level of depression (3.79), for the level of anxiety (3.08) and forthe level of stress were found to be (3.77). There was significant association between the level of depressionand type of diet (?2 = 22.84) and the level of stress and age (?2= 33.44) of the hypertensive patients. Thestudy concludes that most of the hypertensive patients were normal in the level of depression, anxietyand stress. Nurses when we confront patients with hypertension, if they have symptoms of depression,stress and anxiety, we have to refer them for psychiatric consultation and provide health education on stressmanagement strategies.